2022
DOI: 10.3389/fonc.2022.999302
|View full text |Cite
|
Sign up to set email alerts
|

3D CRISPR screen in prostate cancer cells reveals PARP inhibitor sensitization through TBL1XR1-SMC3 interaction

Abstract: Poly(ADP-ribose) (PAR) polymerase inhibitors (PARPi) either have been approved or being tested in the clinic for the treatment of a variety of cancers with homologous recombination deficiency (HRD). However, cancer cells can develop resistance to PARPi drugs through various mechanisms, and new biomarkers and combination therapeutic strategies need to be developed to support personalized treatment. In this study, a genome-wide CRISPR screen was performed in a prostate cancer cell line with 3D culture condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Gastric tissues and cells that were resistant to cisplatin displayed an evident boost in TBL1XR1 expression ( 53 ). CRISPR screen experiments identified TBL1XR1 as a candidate gene associated with PARP inhibitor resistance in prostate cancer cells ( 54 ). A greater sensitivity to the PARP inhibitor olaparib was caused by TBL1XR1 deletion ( 54 ).…”
Section: Oncogenic Functions Of Tbl1xr1 In Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…Gastric tissues and cells that were resistant to cisplatin displayed an evident boost in TBL1XR1 expression ( 53 ). CRISPR screen experiments identified TBL1XR1 as a candidate gene associated with PARP inhibitor resistance in prostate cancer cells ( 54 ). A greater sensitivity to the PARP inhibitor olaparib was caused by TBL1XR1 deletion ( 54 ).…”
Section: Oncogenic Functions Of Tbl1xr1 In Cancersmentioning
confidence: 99%
“…CRISPR screen experiments identified TBL1XR1 as a candidate gene associated with PARP inhibitor resistance in prostate cancer cells ( 54 ). A greater sensitivity to the PARP inhibitor olaparib was caused by TBL1XR1 deletion ( 54 ). Additionally, in both 2D and 3D culture, the olaparib-resistant cells with TBL1XR1 deletion were more susceptible to olaparib treatment ( 54 ).…”
Section: Oncogenic Functions Of Tbl1xr1 In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al. screened 3D spheroids from an olaparib-insensitive cell line and demonstrated that deficiency in TBL1XR1, a core component of nuclear receptor corepressor, sensitized prostate cancer cells to PARPi ( 250 ). Screens by Tsujino et al.…”
Section: Parpi Resistance In the Context Of Covalent Parylation And N...mentioning
confidence: 99%